La cession générale de créances commerciales à titre de garantie comme contrat de « fiducia » en droit québécois, français et anglais - Rhéaume, Jean (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
General assignment of book debts is a frequently used financing contract. Jurisprudence and doctrine have not yet determined its juridical nature in a sure and definitive way. They have qualified it as a pledge, a conditional sale, a giving in payment, a mortgage, a cession en pleine propriété à titre de garantie. Proposed in Quebec, France and England, these various qualifications nevertheless indicate that identital contracts having an identity of finality must correspond to a unity of juridical nature. The author then observes that this contract could well be a fiducia cum creditore or contract of fiduciary transfer already known in Roman Law.